Vertex operators and Jordan fields - Ferreira, L. A. [UNESP]; Gomes, J. F. [UNESP]; Zimerman, A. H. [UNESP] (Elsevier, 1988)
The construction of Lie algebras in terms of Jordan algebra generators is discussed. The key to the construction is the triality relation already incorporated into matrix products. A generalisation to Kac-Moody algebras in terms of vertex operators is proposed and may provide a clue for the construction of new representations of Kac-Moody algebras in terms of Jordan fields. © 1988.